2006
DOI: 10.1002/anie.200601742
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Oxidation of Olefins Catalyzed by a Chiral Bishydroxamic Acid Complex of Molybdenum

Abstract: Excellent yields and enantioselectivities can be achieved in the molybdenum–bishydroxamic acid catalyzed asymmetric oxidation of olefins in air at room temperature with an achiral oxidant (see scheme; acac=acetylacetonate). A range of terminal, cis‐, and trisubstituted olefins can be used as the substrate. Furthermore, when there are multiple double bonds, the most electron‐rich is oxidized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 37 publications
0
35
1
Order By: Relevance
“…aEpoxidation procedures: entry 1 (ref (20a)), entry 2 (ref (21)), entry 3 (ref (22)), entry 4 (ref (23)), entry 5 (ref (24)), entry 6 (ref (25)), entry 7 (ref (26)), and entry 8 (ref (27)).bCombined, isolated yield.cMeasured by NMR.d>90% unreacted 1 recovered.ena, not applicable or no analysis.…”
Section: Resultsmentioning
confidence: 99%
“…aEpoxidation procedures: entry 1 (ref (20a)), entry 2 (ref (21)), entry 3 (ref (22)), entry 4 (ref (23)), entry 5 (ref (24)), entry 6 (ref (25)), entry 7 (ref (26)), and entry 8 (ref (27)).bCombined, isolated yield.cMeasured by NMR.d>90% unreacted 1 recovered.ena, not applicable or no analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of enantioselectivity was put down to the following reasons: (1) perhaps there were other chiral or achiral Mo(VI) peroxy or peroxo species in solution competing with the principal oxoperoxy complex (multiple catalytically active species, which had been alluded to by Mitchell and Finney [23]), (2) the labile nature of the peroxy appendage, particularly at the high temperature applied during the reaction, leading to the generation of a number of competing diastereomeric transition states and (3) fast on/off exchange of the ligands or part of the ligands from the coordination sphere of the Mo(VI) peroxy complex. In fact, weak coordination was suggested recently by Yamamoto and co-workers [24] to explain the lack of success achieved with this epoxidizing system and Chong and Sharpless had also suggested that there might be exchanges between coordinated alkyl hydroperoxides and alkoxides [20] which has recently been substantiated by Veiros et al [25] on the basis of some DFT calculations.…”
Section: Chiral Oxoperoxomolybdenum(vi) Complexes and The Enantioselementioning
confidence: 89%
“…The Mo-BHA complex successfully performed the catalyzed asymmetric oxidation of mono, di-, and tri-substituted olefins under mild conditions in air at room temperature to give epoxides in high yields and up to excellent selectivity. 9 In early experiments of the epoxidation of olefin 18, we found that ligand 3c provided a higher selectivity over ligand 3a in the presence of aqueous TBHP (Table 6, entries 1-2). Changing the oxidant to CHP or tritylhydroperoxide (THP) did improve the selectivity, but reactivity was slower when bulkier THP was utilized.…”
Section: Asymmetric Epoxidation Of Olefinmentioning
confidence: 92%